Կրկին հայոց բդեշխությունների գլխավոր գործառույթի մասին - Aleksan Hakobyan (Banber Arevelagitut'yan Instituti)
At present, it can be assumed with great confidence that the main function of the Armenian pitiashkhs-governorships was military. They were responsible for protecting the external border of neighboring small allied states, and in this matter the entire army of the satellite state was subordinate to them. Thus, the pitiashkhs of Gugarq were responsible for protecting the external border of the kingdom of Iberia (Virq), the pitiashkhs of Ałdzniq were responsible for protecting the external border of the kingdom of Osroene (Edessa), the pitiashkhs of the Nor-Shirakan sides were responsible for protecting the external border of the kingdom of Adiabene (Assyria), and the pitiashkhs of Korduq were responsible for protecting the external border of the kingdom Aruastan (Migdonia). As compensation for their service, the pitiashkhs received control over small areas of the neighboring satellite states. Probably, such an Iranian institution of pitiashkhs was introduced in Armenia by Tigran II during the acceptance of the rights and duties of the king of kings. Analysis of information from Armenian sources shows that several border principalities / governorships also had similar pitiashkh functions. Thus, specific relations were formed between some individual pitiashkhs of the Armenian Kingdom (the bdeašxs) and neighboring states, which sometimes led to separatist tendencies. One of the striking examples of this is the relationship between the Armenian principalities / governorship of Gardman on the right bank of the Kura River and the kingdom of Albania Proper on the left bank of the Kura. In the 4th century the principalities / viceroyalties of the Eastern side of Armenia (Gardmanatsiq and Gorozuayq - “Gargaratsiq” who were separated from Syuniq) - on behalf of the king of Greater Armenia, performed military pitiashkh functions with respect to the Albanian and Bağasakan kingdoms on the left bank of the Kura, bearing supreme responsibility for the protection of their external (northern) borders.